2014
DOI: 10.1292/jvms.14-0146
|View full text |Cite
|
Sign up to set email alerts
|

Visible, Safe and Certain Endotracheal Intubation Using Endoscope System and Inhalation Anesthesia for Rats

Abstract: Anesthesia strongly influences laboratory animals, and it can also greatly affect the experimental data. Rats rank only second to mice in the number used in research fields, such as organ transplantation, regenerative medicine and imaging. Therefore, appropriate and effective anesthesia, including the protocol of the endotracheal intubation and inhalation anesthesia, is crucial. Hence, we evaluated these methods in this study. Twelve Wistar rats were intraperitoneally injected with M/M/B: 0.3/4/5, comprising o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In mice, combination of midazolam and butorphanol, along with medetomidine was used as injectable anesthesia in mice [ 16 , 17 ]. Furthermore, recent rat study demonstrated that the combination of medetomidine, midazolam, and butorphanol can be used as anesthesia induction during tracheal intubation prior to inhalant anesthesia [ 18 ]. Considering these reports, we selected a combination of midazolam and butorphanol as the pre-anesthetic of isoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, combination of midazolam and butorphanol, along with medetomidine was used as injectable anesthesia in mice [ 16 , 17 ]. Furthermore, recent rat study demonstrated that the combination of medetomidine, midazolam, and butorphanol can be used as anesthesia induction during tracheal intubation prior to inhalant anesthesia [ 18 ]. Considering these reports, we selected a combination of midazolam and butorphanol as the pre-anesthetic of isoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…After the recording under the set at 5%, the rat was relieved from anesthesia by removing the nose mask and observed until awakening. Endotracheal intubation in rats requires a certain amount of skill and endoscope for the successful intubation [20] and there were many reports using nose mask for isoflurane anesthesia in rats even in recent years [1, 2, 7, 40]. For practical data using nose mask, we used nose mask instead of endotracheal intubation in maintenance of isoflurane anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…However, it was demonstrated that the tracheal smooth muscle of rats submitted to the intubation procedure showed no histological signs of injury (KONNO et al, 2014). It seems that the relatively short period in which the animal is subjected to the procedure is not enough to cause damage to the tracheal smooth muscle.…”
Section: New Technique Intubationmentioning
confidence: 99%
“…Aiming at achieving intubation, several techniques are described in the literature, although some require more elaborate equipment specially developed (CLARY et al, 2004;KASTL et al, 2004;KONNO et al, 2014), requiring little prior training and generally achieving high success rates. Other simpler methods, not requiring specific materials, however, require more training and have questionable success rates, as well as injury history in the glottis, larynx and/or vocal cords of animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation